Ekstrak Pegagan Meningkatkan Titer Antibodi Mencit Setelah Diinfeksi Salmonella typhi (CENTELLA ASIATICA EXTRACT INCREASE ANTIBODY TITER IN MICE AFTER SALMONELLA TYPHI INFECTION) - Besung, I Nengah Kerta; Astawa, I Nyoman Mantik; Suatha, I Ketut; ., Hartaningsih (Jurnal Veteriner; Vol 14 No 2 (2013), 2013)
A study was conducted to find out the ability of Centella asiatica (C. asiatica) in enhancing antibodyresponse of C. asiatica treated mice following Salmonella typhi (S. typhi) infections. It is therefore expectedthat herbal drug such as  C. asiatica  can be used as an alternative medicine to prevent and to curesalmonellosis both in animals and human. Experimental laboratory studies were conducted usingCompletely Factorial Randomized Design. Mice were divided into four groups and they were treatedrespectively with destilated water (negative control), 125, 250, and 500 mg/kg BW/day of  C. asiaticaextract. The treatment was conducted daily for two weeks  and the mice were inoculated with 105 cells/mlof  S. typhi. The antibody response were examined by indirect enzyme-linked immunosorbent assay (ELISA)on first day, second week and fourth week  after S. typhi infections.  The result showed that treatment ofmice with C. asiatica extract significantly (p<0,05) enhanced antibody titer of Balb/c mice after S. typhiinfections. The highest antibody titer was observed at four weeks after S. typhi infections with 500 mg/kgBW/day (94,0370 ± 1,69 IU).
Keywords: pegagan, C. asiatica, antibody, S. Typhi